1998
DOI: 10.1097/00003246-199802000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial durability and rare ultrastructural colonization of indwelling central catheters coated with minocycline and rifampin

Abstract: Coating catheters with minocycline and rifampin inhibits ultrastructural colonization of indwelling catheters and maintains effective antimicrobial activity for at least 2 wks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(44 citation statements)
references
References 22 publications
0
43
0
1
Order By: Relevance
“…27 Catheters treated with minocycline and rifampin may have antimicrobial activity extending up to 2 and possibly up to 4 to 6 weeks. 25 This inconsistency may be interpreted as evidence of specific antibiotic activities. Further randomized trials are needed to establish the effect of different antibiotic coating methods on the long-term anti-infective efficacy of CVCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27 Catheters treated with minocycline and rifampin may have antimicrobial activity extending up to 2 and possibly up to 4 to 6 weeks. 25 This inconsistency may be interpreted as evidence of specific antibiotic activities. Further randomized trials are needed to establish the effect of different antibiotic coating methods on the long-term anti-infective efficacy of CVCs.…”
Section: Discussionmentioning
confidence: 99%
“…50 There was no evidence for time dependency of antibiotic-coated devices because no trials reporting on longer average insertion times could be retrieved. If the antimicrobial efficacy of antibiotic-coated catheters should indeed extend to 2 to 4 weeks, 13,25 an exchange of them after 7 days might not be necessary. However, this needs to be confirmed in randomized, controlled trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A biofilm-infected implant often must be removed and replaced, placing the patient at increased risk for complications due to these additional procedures (5,32). Current antimicrobial therapies for biofilms have largely proven unsuccessful (15), and the exact explanation for these treatment failures is still unclear (9).…”
Section: Staphylococcal Infections Of Both Staphylococcus Aureus Andmentioning
confidence: 99%
“…Lysostaphin bridges this twostep process by both disrupting the S. aureus and S. epidermidis biofilms and killing the released bacteria. It has been shown that coating medical implants with antimicrobials may effectively prevent the initial adherence of staphylococcal biofilms to the implants (29,32,37). Coating biomedical materials with lysostaphin may also prove successful in preventing early adherence of staphylococci to the implants, thus averting biofilm formation.…”
mentioning
confidence: 99%